MODUL DAN TEKNOLOGI DALAM FLEKSIBILITAS RUANG DI KOTA METROPOLITAN JAKARTA - Setiadi G S (Jurnal Dimensi Seni Rupa dan Desain, 2008)
AbstractBuilding as part of city planning in architecture play an important role in shopping architectural apperance so that the image and the outer look of the buildings become an essential part in public buiding such as schools and offices. To gain a good design of the building which meets the architectural standard a well-planned design of the building should be carefully considered -either in governmental buildings or commercial buildings . The design in buiding must involve dimensial standard which is a part of the process of designing buildings must involve dimensial satndard which is a part of the process of designing buildings without neglecting the essensce of the design itself. Good design should be viewed from its function and its aesthetics. Flexibility is the capacity to accept changes towards space without completely changing the main element which form that space. The changes simply exist in supporting element AbstrakBangunan sebagai bagian dari arsitektur kota menjadi sangat penting dalam pembentukan wajah arsitektur , sehingga aspek citra dan penampilan bangunan juga menjadi hal sangat penting untul diperhatikan baik bangunan fasuilitas pendidikan, perkantoran, dan bangunan-bangunan lainnya. Untuk mencapai perancangan bangunan yang memenuhi standar arsitektur yang baik tentunya harus memalui proses perancangan yang matang, baik untuk keperluan penyelengaraan pemerintah maupun banguan komersial. Pernacangan dalam bangunan akan dihadapkan pada maslah-maslah dimensi ukuran yang merupakan bagian dari satandar proses perancangan tanpa harus meninggalkan nilai-nilai desain yang baik ditinjau dari segi fungsi dan estetika. Fleksibitas adalah kemampuan suatu ruang untuk menerima perubahan-perubahan terhadapr fungsi ruang tersebut, tanpa meribah keseluruhan elemen pembentuk ruang di mana perubahan hanyalah pada elemen-elemen pengisinya saja